Identification of novel QTL for leaf traits in soybean. Issue 1 (18th October 2013) - Jun, Tae‐Hwan; Freewalt, Keith; Michel, Andy P.; Mian, Rouf; Singh, R.
Abstract Several leaf traits of soybean (Glycine max L. Merr.), including leaf area (LA), leaf shape (LS) and specific leaf weight (SLW) may be related to soybean yield. The objective of this study was to identify novel quantitative trait loci (QTL) for LA, LS and SLW in a recombinant inbred line (RIL) population. The phenotype data were collected in 2011 and 2012 for 93 F7:10 RILs using a randomized complete block design with 2 replicates each year. Five hundred and sixteen single‐nucleotide polymorphism (SNP) markers and the phenotype data were used to detect QTL using single marker analysis (SMA) and composite interval mapping (CIM). Single markers analysis identified 26 QTL for the three traits, of which 17 were novel and the rests were previously reported QTL. Most of these QTL were also identified by CIM. Most QTL reported in this study were in close proximity (<1 cM) of one or more SNP markers. These publicly available SNP markers with close linkage to LA, LS and SLW should be useful for marker‐assisted breeding for these traits.